The Validity of the Interpersonal Behaviors Questionnaire (IBQ) in Sport - Rocchi, Meredith; Pelletier, Luc; Desmarais, Philippe (Measurement in physical education and exercise science, 2017)
According to Self-Determination Theory (SDT), basic psychological needs will be influenced by other individuals' interpersonal behaviors. The objective of the present research is to extend the validity of the Interpersonal Behaviors Questionnaire (IBQ and IBQ-Self) to the sport context. The measure was designed to assess perceptions of interpersonal behaviors of others (IBQ) or self-reports of interpersonal behaviors (IBQ-Self) in the context of SDT. This measure consists of 24 items and six subscales looking at autonomy-supportive, autonomy-thwarting (controlling), competence-supportive, competence-thwarting, relatedness-supportive, and relatedness-thwarting interpersonal behaviors. In Study 1, athletes were asked to report on their perceptions of their coaches' interpersonal behaviors (IBQ). In Study 2, coaches were asked to report on their interpersonal behaviors when they coach their athletes (IBQ-Self). The results supported that the scale had a strong factor structure, internal consistency, and validity. Overall, the results supported the IBQ and IBQ-Self are valid measures of interpersonal behaviors in sport.